Assessing the impediments to e-learning utilization by higher institution students - Adekunle Thomas Olutola; Rafiu Ademola Olatoye; Olufunke Omotoke Olatoye (Intelektual Pustaka Media Utama, 2021)
This study assessed the impediments to e-learning utilization by higher institution students in Katsina State, Nigeria. Survey type of descriptive research design was used in the study. There were 381 students randomly selected in four higher institutions. A questionnaire with test-retest reliability coefficient of 0.88 was used to gather data from the respondents. The researchers used Frequencies, percentages, means and t-test to analyze the data collected for the study. Findings revealed that all the fifteen impediments investigated in this study affect the e-learning utilization by higher institution students in Katsina State, Nigeria in varying degrees. The foremost factor is money to purchase e-learning resources followed by limited electricity supply. Moreover, significant difference was not found in the impediments to e-learning utilization by higher institution students on the basis of gender (t=-.796, Df=397, P more than 0.05) but significant difference was found in the factors affecting the use of e-learning by students’ of Universities and Colleges of Education (t=-2.969, P less than 0.05). It was recommended that all the identified impediments affecting the e-learning utilization by higher institution students in Katsina State, Nigeria should be addressed by the government.